2011
DOI: 10.4067/s0716-97602011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dendritic cell/T cell interactions to triggering and maintaining autoimmunity

Abstract: Under healthy conditions, there is a balance between tolerance to self-tissue constituents and immunity against foreign antigens. Autoimmunity diseases (AD) take place when that equilibrium is disrupted and the immune response is directed to self-antigens, leading to injury or destruction of host tissues. The mechanisms conducing to the loss of immune tolerance remain largely unknown. The recent appearance of biological therapies has contributed to signifi cant reduction in morbidity. However, currently availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Mature DCs can activate T cells. In contrast, tolerogenic (immature) DCs or monocytes, cells able to differentiate to DCs, can promote T-cell hyporesponsiveness, and induce immune tolerance (46). Therefore, tolerogenic DCs or monocytes have emerged as an attractive therapeutic target, because they can induce antigen-specific tolerance without provoking general, widespread immunosuppression.…”
Section: Innate Immunity In Slementioning
confidence: 99%
“…Mature DCs can activate T cells. In contrast, tolerogenic (immature) DCs or monocytes, cells able to differentiate to DCs, can promote T-cell hyporesponsiveness, and induce immune tolerance (46). Therefore, tolerogenic DCs or monocytes have emerged as an attractive therapeutic target, because they can induce antigen-specific tolerance without provoking general, widespread immunosuppression.…”
Section: Innate Immunity In Slementioning
confidence: 99%
“…Similarly, peripheral tolerance to tissue specific antigens could be achieved by the homeostatic presentation of autoantigens by immature DCs in the draining lymph node [ 216 ]. Different immune cell interactions could take place in lymph nodes to promote tolerance [ 217 , 218 ]. It has been demonstrated that in lymph nodes from NOD mice, Tregs prevent the interaction and cell arrest of effector T cells with DCs, reducing autoimmune responses [ 217 ].…”
Section: Designing New Therapies Based On Tolerogenic Dcsmentioning
confidence: 99%
“…Dendritic cells (DCs) are the most potent antigen-presenting cells in the immune system. After capture of foreign antigens, they migrate to the lymphoid organs where DCs become mature and present antigens to naïve T cells to elicit the effective adaptive immune response (Llanos et al, 2011;Xuan et al, 2016). These mature DCs are then induced to undergo apoptosis and disappear from the lymph nodes (LNs) (Llanos et al, 2011;Xuan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After capture of foreign antigens, they migrate to the lymphoid organs where DCs become mature and present antigens to naïve T cells to elicit the effective adaptive immune response (Llanos et al, 2011;Xuan et al, 2016). These mature DCs are then induced to undergo apoptosis and disappear from the lymph nodes (LNs) (Llanos et al, 2011;Xuan et al, 2016). The apoptosis is initiated through two major apoptotic pathways: the death receptor-mediated extrinsic pathway and the mitochondrial-involved intrinsic pathway (Martino, 2007).…”
Section: Introductionmentioning
confidence: 99%